Krátké ohlédnutí za vývojem početnosti velkých šelem - Kunc, Ludvík , 1934-
Článek shrnuje vývoj populací velkých druhů šelem v chráněné krajinné oblasti Beskydy za uplynulých 10 let a přibližuje novinky ze života tamní populace rysa ostrovida (Lynx lynx). This article summarizes the development of large predator species populations in the Beskydy Protected Landscape Area over the last 10 years, and presents the latest developments in the lives of the local population of the Eurasian Lynx (Lynx lynx). Ludvík Kunc.